Testing the Cognitive Retroactive Transfer Hypothesis: Evidence from Moroccan University Readers - Noureddine Atouf; Meriem Harrizi (Yayasan Visi Intan Permata, 2024)
The extant study extrapolates the principles of the Cognitive Retroactive Transfer hypothesis, a theory of reading transfer between languages recently introduced to the literature, in an academic context. Forty-five freshmen are recruited from the English Department at the School of Arts and Humanities Ben M’sik (Hassan II University of Casablanca). The study employs a quasi-experimental design which involves two main phases: pre-intervention and post-intervention. The participants are selectively allocated to an experimental group (n=25) and a control group (n=20). The experiment measures the transferability of improved metalinguistic awareness from English (the foreign language “FL”) to Arabic (the first language “L1”). To this end, a battery of reading tests is administered in both languages before and after the intervention. Upon completing the pretest phase, the experimental group receives a three-month training, targeting core metalinguistic skills. To compare pretest and posttest scores, a multivariate analysis of variance (MANOVA) is conducted to check the groups’ overall differences across the set of reading skills before using Simple Group Contrasts (k-matrix) as a follow-up test to analyze the groups’ performance on each reading skill. The results show a positive effect of the intervention on the experimental group’s performance over all the skills except orthographic knowledge posttest scores which level off. The findings give more prominence to the CRT hypothesis which has been solely tested in children bilingual settings. The unchanged orthographic knowledge scores suggest the essential role of explicit print exposure and practice in developing spelling skills in another language. The ongoing research paper calls for adopting fine-grain and level-fitting pedagogical approaches to address reading difficulties at university levels.